Race and respect - Kee, Alistair (Scottish journal of theology, 2009)
I am grateful to Robert Beckford for the care he has taken to present the argument of my book and for his incisive comments and criticisms. My book has been reviewed by other black theologians, in the UK and the USA, who have avoided the argument of the book, preferring to play the race card: any criticism of black theology can only be an expression of white racism. I am grateful to the editors of SJT in affording me the opportunity to respond. It would be tedious to become involved in a detailed exchange of he-said–I-said. I have chosen to respond to two issues raised in Beckford's review.